PERILAKU SOSIAL JALAK BALI (Leucopsar rotschildii Stresemann 1912) DI KANDANG PERKEMBANGBIAKAN UNIT PENGELOLAAN KHUSUS PEMBINAAN JALAK BALI TEGAL BUNDER TAMAN NASIONAL BALI BARAT - Sonia Wulandari; andi chairil ichsan; Maiser Syahputra (Forestry Study Program University Of Mataram, 2019)
Management of breeding activities consists of feed aspect, sex ratio, reproduction, health, and other needs. Jalak social behavior in UPKPJB Tegal Bunder consists of 9 behaviors consisting of interdisciplinary behavior, approaching each other, making out, marrying, cleaning the beak, chasing each other, pecking each other, mutual voices and nursery care. From the observation, there is some male and female behavior. The highest social behavior is performed by females about 420 times, while males are about 388 times during observation time.